Sustainable Fashion Values as a Personal Branding Strategy on @Sashfir’s Tiktok Account - Sadida, Fila; Dias Adiprabowo, Vani (Humaniora: Journal of Indonesia Culture and Society, 2026)
This research examines the rising demand for sustainability in the fashion industry and how social media platforms, particularly TikTok, provide a space for content creators to embed sustainable values into their personal branding. The research addresses a gap in academic discourse on the strategic application of sustainability principles to shape digital identity. The central question explored is: how does the TikTok account @sashfir integrate sustainable fashion values into its personal branding strategies? Using a qualitative instrumental case study approach, this research applies Montoya and Vandehey’s personal branding theory. Data are collected through content observation on TikTok, focusing on visual identity, product selection, and consistency in presenting sustainability practices. The findings reveal that @sashfir consistently constructs a self-image centered on sustainable fashion, as evidenced by eco-conscious product choices and authentic communication. The branding strategy prioritizes visual coherence and message consistency but lacks strong emotional engagement, which limits its depth of influence. The originality of this research lies in its focus on integrating sustainability into personal branding on creative platforms such as TikTok, a topic that remains underexplored in the academic literature. This research suggests that sustainability can be strategically implemented to build authentic, meaningful personal branding, particularly for creators seeking to align with environmental consciousness. However, as this research focuses on a single case, further research involving multiple creators and audience analysis is recommended to enrich the findings and strengthen the generalizability of the conclusions.